Hybridization of α-zirconium phosphate with hexachlorocyclotriphosphazene and its application in the flame retardant poly(vinyl alcohol) composites. (November 2016) - Xu, Lingfeng; Lei, Caihong; Xu, Ruijie; Zhang, Xiaoqing; Zhang, Feng
Abstract: A planar-like inorganic α-zirconium phosphate (α-ZrP) particles were modified by a kind of cyclophosphazene derivative via three-step hybridization method, first modified by melamine (MA), then combined with hexachlorocyclotriphosphazene (HCCP) through nucleophilic substitution and further integrated with excessive MA. Thus, a hybrid flame retardant (HAC) was successfully synthesized. The composites based on poly(vinyl alcohol) (PVA) and HAC were prepared by solution blending. The thermal, mechanical properties and flame retardancy of the composites were studied. It was found that HAC showed a catalytic effect in the initial decomposition stage and promoted the formation of char at high temperatures. When the content of HAC was 15 wt%, the limiting oxygen index (LOI) reached 28.4% and classified V-0 rating, whereas with the same content of fire retardant, for PVA/α-ZrP and PVA/product of MA with HCCP composites (one kind of intumescent flame retardant IFR), the LOI values were only 24.7% and 27.1%, respectively. The combination of IFR and α-ZrP could remarkably improve the yield and graphitization of char residues, make the char more stable, compact and continuous, inhibiting underlying PVA from contacting heat and oxygen. Moreover, the mechanical properties could be reinforced and toughened with certain content of HAC.